PERTUMBUHAN AGENS HAYATI Trichoderma harzianum DENGAN BERBAGAI TINGKAT DOSIS PADA BEBERAPA JENIS KOMPOS - A A Likur; Abraham Talahaturuson; Wilhelmina Rumahlewang (Universitas Pattimura, 2016)
This research was made in July to September 2016 in Plant Disease Laboratory, Agriculture Faculty, Pattimura University, Ambon. This research was made with purpose to get the best compost as a carrier of Trichoderma harzianum. The research method was experiment method using completely randomized program (RAL) using two factors, i.e three treatments with three repetitions, therefore 27 unit specimen were found. Based on observation in the laboratory, the result were: 1) a growth and best dense of T. harzianum spore in compost was in 10 % dose; 2) Compost produced by Farmers’ group Sumber Wiji Kairatu was the best for T. harzianum with pH grade of 7.5; and 3) Best compost formulation as a carrier for control agent T. harzianum was produced by Farmers’ group Sumber Wiji Kairatu with 10 % dose.